CCR2 downregulation attenuates spinal cord injury by suppressing inflammatory monocytes. Issue 5 (6th November 2020) - Zhang, Qingpu; Zhu, Chunjing; Li, Xiaojing; Shi, Yulin; Zhang, Zhongli
Abstract: Specific elimination of blood‐derived macrophages/monocytes following spinal cord injury (SCI) may suppress neurotoxicity without affecting the neuroprotective microglia at the injury sites. We aimed to deplete hematogenous monocytes by downregulating CCR2 through siCCR2‐loaded nanoparticles and investigated its outcome in the recovery of locomotor function of SCI mice. We induced SCI in mice and examined the influx of blood‐derived monocytes into the injury site. We constructed nanoparticles loaded with siRNA targeting CCR2 and examined its efficiency in downregulating the CCR2 expression in cultured RAW264.7 cells and monocytes in vivo. Finally, we assessed the effects of CCR2 downregulation in pro‐inflammatory cytokine production, axon regeneration, and locomotor recovery of the SCI mice. We found that SCI significantly increased the CCL2 expression and number of blood‐derived macrophages/monocytes in the lesion area. Nanoparticles loaded with siCCR2 significantly suppressed the CCR2 expression in hematogenous macrophages/monocytes, reduced the number of hematogenous macrophages/monocytes, and reduced pro‐inflammatory cytokine production at the injury site. Finally, CCR2 downregulation promoted axon regeneration and improved locomotor recovery in SCI mice. Our study suggests that siCCR2 loading nanoparticles are efficient and specific in downregulating hematogenous macrophages/monocytes without affecting the neuroprotective microglia and its efficacy in promoting locomotor recovery in SCI mice warrants further investigation for its clinical application in SCI. Abstract : siCCR2 loading nanoparticles is an efficient and specific tool to downregulate hematogenous macrophages/monocytes without affecting neuroprotective microglia and its efficacy in promoting locomotion recovery in SCI mice warrants further investigation for its clinical application in SCI.